Primary Percutaneous Coronary Intervention in a 24-hour PCI Capable Hospital in Indonesia - Laksono, Sidhi; Hosanna, Cliffian; Angkasa, Irwan Surya; Nurbaeti, Putri (UNUSA Press, 2025)
Introduction: Chest pain may be a symptom of a life-threatening disease such as S ST-Elevation Myocardial Infarction (STEMI). Immediate primary percutaneous coronary intervention (PPCI) is recommended for virtually all STEMI patients who present in a PCI-capable hospital. Objective: We would like to present data on Door-to-Balloon (DTB) times and the factors affecting it. Methods: This is a single-center retrospective study. Patients are STEMI patients, undergoing primary PCI from 1st January 2024 to 30th April 2024. Secondary data are obtained from the medical records and analyzed. Results: A total of 60 patients undergo PPCI during the study period. Patients are generally male patients, aged 53.67 years old, with 2 traditional cardiovascular risk factors, presenting to the emergency department (ED) with an average of 5.88 hours of chest pain. DTB time was 86.25 minutes during the study period. We identified the onset of chest pain and referred patients to be associated with DTB time. Referred patients had longer onset since chest pain but faster DTB time. We found no association between age, gender, presenting time, diagnosis, Killip class, and physician factor to significantly affect DTB time. Conclusions: We have identified factors that may help us improve our DTB time. Patient knowledge should also be improved to increase awareness of symptoms of chest pain, minimizing patient delay and improving total ischemic time.